ALGORITHM FOR INTRODUCING MOTIVATION MANAGEMENT IN ORGANIZATIONS - Lyutko, Oksana (Mountain School of Ukrainian Carpaty, 2021)
The article notes that in modern conditions managers of all types of organizational resources primarily rely on human resources. This means that the improvement of the functioning of organizations can be achieved primarily through their better use and presupposes the purposeful activity of managers in this direction, including the motivation of the labor behavior of personnel. However, quite often, managers use such methods of influencing the professional behavior of employees, leading to demotivation of their activities. In our opinion, this situation is explained by the discrepancy between the perception of managers about the factors affecting the work of employees and the real situation. In this regard, it is very important for managers to be able to rethink their managerial experience, to overcome their own stereotypical ideas about the motivation of the activities of employees, and as a result – to form modern managerial relationships in the team, using motivational management. That is why our purpose is to determine the algorithm for the implementation of motivational management in any organization. The object of the research is the theoretical and methodological foundations of motivational management. On the basis of a critical analysis of scientific research and publications which defined the essence of the concept of «motivational management» was made an attempt to present its author’s formulations, object and subject. With the help of a questionnaire, the factors that affect the quality of performance of professional duties of employees mostly, are identified, the features of their motivation are analyzed. Considering motivational management as one of the most effective types of modern management and providing for the process of internal management of the activities of the organizations, as a result, an algorithm for the implementation of the project was determined.